Workshop on STI and rural radio services: a real priority not just a need - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Workshop on STI and rural radio services. rural broadcasters from 18 ACP countries in the capital city of Burkina Faso from May 15 to 18 1989